2022
DOI: 10.1002/jbm4.10635
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Inflammatory Macrophage Populations Sequentially Infiltrate Bone‐to‐Tendon Interface Tissue After Anterior Cruciate Ligament (ACL) Reconstruction Surgery in Mice

Abstract: Macrophages are important for repair of injured tissues, but their role in healing after surgical repair of musculoskeletal tissues is not well understood. We used single-cell RNA sequencing (RNA-seq), flow cytometry, and transcriptomics to characterize functional phenotypes of macrophages in a mouse anterior cruciate ligament reconstruction (ACLR) model that involves bone injury followed by a healing phase of bone and fibrovascular interface tissue formation that results in bone-to-tendon attachment. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…However, immune activation can take several forms, and not all forms of inflammation are equivalent. Diversity of immune function is well characterized in wound healing in tissues such as skin and lung, but far less is known about the diversity of immune mechanisms that regulate healing in load-bearing musculoskeletal tissues after injury [31][32][33]. The current study showed that following every form of surgical intervention, the cartilage responded with greater immune activation than the synovium in mid-term osteoarthritis after adjusting for baseline differences between the tissues.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, immune activation can take several forms, and not all forms of inflammation are equivalent. Diversity of immune function is well characterized in wound healing in tissues such as skin and lung, but far less is known about the diversity of immune mechanisms that regulate healing in load-bearing musculoskeletal tissues after injury [31][32][33]. The current study showed that following every form of surgical intervention, the cartilage responded with greater immune activation than the synovium in mid-term osteoarthritis after adjusting for baseline differences between the tissues.…”
Section: Discussionmentioning
confidence: 62%
“…Beyond modeling the joint response to ACL injury, previous animal models of ACL transection followed by ligament reconstruction have featured RNA sequencing of several knee joint tissues (e.g., bone, tendon, cartilage, synovium) [33,41,42]. characterized cartilage and synovium transcriptomes in a porcine model at one and four weeks following ACL transection, with and without reconstruction [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, H2-Aa is a histocompatibility class-II antigen A, which enables peptide antigen binding activity and is involved in the response to interferon gamma. Although further studies are necessary to fully elucidate the roles of these individual genes, addressing the interferon response in particular could be promising for further investigation, as interferons have previously been reported to promote injury-associated inflammation, suppress collagen synthesis, and inhibit fibroblast proliferation [45][46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…ACL injury models fall into three categories: (i) surgical ACL transection, (ii) noninvasive ACL rupture, and (iii) ACL transection and reconstruction. Due to the limited size, direct surgical repair of the ACL is less commonly performed in rodents 14,15,18–28,38 . ACL transection procedures offer great control over the extent of the injury while minimizing damage to adjacent tissues.…”
Section: The Aclmentioning
confidence: 99%